2019
DOI: 10.1111/exd.13877
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma types by in vivo reflectance confocal microscopy correlated with protein and molecular genetic alterations: A pilot study

Abstract: Cutaneous melanoma (CM) is one of the most prevalent skin cancers, which lacks both a prognostic marker and a specific and lasting treatment, due to the complexity of the disease and heterogeneity of patients. Reflectance confocal microscopy (RCM) in vivo analysis is a versatile approach offering immediate morphological information, enabling the identification of four primary cutaneous RCM CM types. Whether RCM CM types are associated with a specific protein and molecular genetic profiles at the tissue level r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
5
0
1
Order By: Relevance
“…On the other hand, molecular studies support the view that melanoma comprises distinct types of tumors and suggest that specific morphological features may help predict its clinical behavior. In line with this, and given some dermoscopic attributes of melanoma, such as features of regression and vascularity, were strongly linked to the overall amount of genomic damage [24].…”
Section: Discussionsupporting
confidence: 57%
“…On the other hand, molecular studies support the view that melanoma comprises distinct types of tumors and suggest that specific morphological features may help predict its clinical behavior. In line with this, and given some dermoscopic attributes of melanoma, such as features of regression and vascularity, were strongly linked to the overall amount of genomic damage [24].…”
Section: Discussionsupporting
confidence: 57%
“…Filipp et al demonstrated that the expression of CD271 regulates melanoma cell stemness and serves as a driver of metastasis [ 16 ]. Furthermore, we previously demonstrated that, besides other markers, CD271 is suggestive of a progression and an increase in the aggressiveness of melanomas, according to their morphologies [ 12 , 26 ]. Verykiou et al demonstrated that the treatment of CD271-expressing melanoma subpopulations with RNA interference and small-molecule inhibitors of CD271 slowed down the development of MEKi resistance [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, superficial spreading melanoma (SSM) represents the most common form of melanoma in Caucasians while NM is less represented [37,38]. RCM variations corresponding to changes in each skin layer can be observed and a melanoma classification according to RCM features, corresponding to different molecular alterations, has been established [39,40].…”
Section: Main In Vivo Clsm Diagnostic Clues In Skin Cancersmentioning
confidence: 99%